Alexandria - Feldmeier, Reinhard; Albrecht, Felix; Georges, Tobias; Kaden, Manuel; Martsch, Christoph; Feldmeier, Reinhard; Georges, Tobias; Kaden, Manuel; Martsch, Christoph (Mohr Siebeck, 2013)
Alexandria.
PublicationDate: 20240513
Keywords: Religion -- Bildung -- Alexandria -- Neues Testament -- Kirchengeschichte -- Antike Religionsgeschichte -- Array